Assessment Analysis of AKM (Assessment Competency Minimum) and Character Surve in School - Jauhar Syarifah; Indah Aminatuz zuhriyah; Reti Suryani; Tri Retno Khalista Sari (Universitas Muhammadiyah Enrekang, 2023)
Indonesian Minister of Education and Culture Nadiem Makarim conveyed his perspective on #MerdekaBelajar. Replacing the National Standard School Examination (USBN) with a Minimum Competency Assessment and Character Survey is one of the goals. Literacy, numeracy, and character are the three elements that are evaluated. In order to be able to assess the concept and its application, this concept must be explored by linking it to pre-existing educational concepts. Through qualitative research, the literature study shows the concept of AKM assessment. The procedure for assessing AKM is to evaluate students' competence in reading literacy and numeracy, where each subject is rich in literature so that it is very possible to develop it in AKM and the Numerical Literacy Assessment in AKM can also be a reference in development. assessment.